Comparison of LED technology with High-Pressure Sodium Lamp System - Andrej Djuretic, Nebojsa Arsic and Mile Petrovic (Journal of Information & Systems Management, 2023)
This work has reviewed briefly the efficiency of LEDs which is dominating the global light systems. It is documented and experienced that the LED is the result of artificial lighting and not much efficient during the outdoor lighting. When we compare this technology, we can conclude that the High-Pressure Sodium Lamps are more powerful.